Trends in seizure hospitalisations pre and post rotavirus vaccine introduction among children in Soweto, South Africa - Omoniyi, Babalola Joseph (My University, 2021)
Introduction Reductions in childhood seizure hospitalisations following rotavirus vaccine introduction have been reported in some countries. This study evaluated the trends in seizure hospitalisation preand post-rotavirus vaccine introduction among children in Soweto, South Africa. Methods This secondary data analysis used an existing Paediatric Discharge Summary database including hospitalised children aged 6-59-months at Chris Hani Baragwanath Academic and Bheki Mlangeni District Hospitals from 1 January 2006 to 31 December 2018. International Classification of Diseases (ICD)-10 code definitions for febrile seizures (FSs), epilepsy, and unspecified seizures (collectively referred to as all-cause seizures [ACS]), acute gastroenteritis (AGE), and acute respiratory tract infections (ARI) were used. Monthly counts and incidence of ACS and FS hospitalisations pre- (2006-2008) and post-rotavirus (2010-2018) vaccine introduction in 2009 were analysed by age-group (6–11-, 12–23-, 24-35-, 36-47-, and 48-59- months). Results Of 74,160 hospitalisation-episodes among 57,161 children, 14,135 (19.0%) ACS hospitalisations (epilepsy, 2,993 [21.0%]; FS, 9,475 [67.0%]; unspecified seizures, 1,679 [11.9%]) occurred in children aged 6-59-months. The overall annual incidence of FS hospitalisations among children aged 6-59-months decreased by 34.2% from 4.79/1,000 (median 2006–2008) to 3.15/1,000 in 2013 but increased subsequently from 5.97/1,000 in 2015 to 7.72/1,000 in 2018. The highest incidence of FS hospitalisations of 11.29/1,000 occurred in 2018 compared to 7.59/1000 (the pre-vaccine years) among the 12-23 months age group. FS hospitalisation occurred in 8.3%, 4.9%, and 1.5% of children hospitalised with ARI, AGE, and HIV infection, respectively; and more than 50%, 60%, and 80% of the children were aged 24-59 months. Conclusions An un-sustained decline in ACS/FS hospitalisation was observed after rotavirus vaccine introduction but any observed changes in FS epidemiology could not be attributed to the impact
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in the field of Child Health, Johannesburg, 2021